RANCANG BANGUN SISTEM INFORMASI LABORATORIUM SMKN 2 PAYAKUMBUH BERBASIS WEB - Sari Rahmadina Anori; Kasman Rukun; Yasdinul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
Laboratory of SMKN 2 Payakumbuh not well organized, whereas all activities in thelaboratory requires administration, so that the laboratory can be functioned optimally. Informationtechnology is one way that can be used to simplify the administrative management of the laboratory.The aim of this research was to design and build a web-based laboratory information system inorder to facilitate the administrative management of the laboratory. Information systemdevelopment methods carried out by the approach of Object Oriented Programming (OOP) anddesigned using system modeling tools. Implementation of this information systems using webprogramming languages PHP, HTML, CSS, and Javascript by using CodeIgniter framework andMySQL as the database server. The information system can be accessed via web browser byteacher as user of goods in laboratory, laboran as laboratory activity manager, engineer asmanager of the broken equipment, and the head of the laboratory in main charge of the laboratory.Web Based Laboratory Information System of SMKN 2 Payakumbuh can help the administrativemanagement of the laboratory to booking, use, return and maintenance of laboratory instruments,manage laboratory activities and preparing reports, so that making the laboratory functioned moreoptimal.Keywords: Laboratory, Web, Information Systems, CodeIgniter